Basic magnetic nanoparticles as efficient catalysts for the preparation of naphthopyrane derivatives. (1st December 2012) - Yarahmadi, Hossein; Shaterian, Hamid Reza
Aminosilane-functionalised spinel ferrite oxide (Fe2O3) magnetic nanoparticles have been synthesised and used as efficient heterogeneous base catalysts for the condensation of aromatic aldehydes with malonitrile and α (or β) naphthole via a three-component reaction under solvent-free conditions at 80 °C. Quantitative conversion of the reactants is achieved under mild conditions. Recovery of the catalyst is easily achieved by magnetic decantation. The supported catalyst is reused four times without significant degradation in catalytic activity. Naphthopyrans are polyfunctionalised benzopyran derivatives that have many biological and pharmacological properties.